Vida Saludable: Hiperglicemia e Hipoglicemia - Jennifer Hillan (EDIS)
FCS8820-Span, a 3-page fact sheet by Jennifer Hillan, is the Spanish version of "Healthy Living: Hyperglycemia and Hypoglycemia" (FCS8820/FY885). It will help patients with diabetes understand how to detect, treat, and prevent hyperglycemia (high blood sugar) and hypoglycemia (low blood sugar). Published by the UF Department of Family, Youth and Community Sciences, January 2007.